The importance of improving chemistry education based on the STEAM approach - Pardayev Ulug'bek Xayrullo o'g'`li; Xoliqulov Hamro Jasur o‘g‘li; Tilyabov Maxsudjon Umurzokovich, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In contemporary education, the integration of Science, Technology, Engineering, Arts, and Mathematics (STEAM) has gained substantial recognition for its capacity to foster innovative thinking and problem-solving skills. This paper investigates the significance of incorporating the STEAM approach into chemistry education, aiming to cultivate a comprehensive understanding of the subject while nurturing creativity and critical thinking among learners.